1983
DOI: 10.1007/bf01625965
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral triplication with a ureterocele

Abstract: Ureteral triplication is a rare anomaly of the upper urinary tract. The occurrence of complete ureteral triplication with an associated ureterocele has only been reported once before. A case of this extremely rare association is described, and the embryology of this condition is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Finkel and Gosalbez reported ureteroceles associated with type I and rarely with type II ureteral triplications [3,4]. In recent review of the literature, Pode [7] and Merlini [6] reported ureteral triplication cases associated with obstruction; however, in the case reported by Merlini et al obstruction was caused by ureteroureteric reflux, while the other one was due to uretero-vesical stenosis [6,7].…”
Section: Discussionmentioning
confidence: 89%
“…Finkel and Gosalbez reported ureteroceles associated with type I and rarely with type II ureteral triplications [3,4]. In recent review of the literature, Pode [7] and Merlini [6] reported ureteral triplication cases associated with obstruction; however, in the case reported by Merlini et al obstruction was caused by ureteroureteric reflux, while the other one was due to uretero-vesical stenosis [6,7].…”
Section: Discussionmentioning
confidence: 89%
“…La anomalía más frecuentemente asociada a la triplicidad ureteral es la duplicidad contralateral (37%) [10][11][12][13][14][15][16][17] , la ectopia ureteral (28%) 14,15,[18][19][20][21] o la displasia renal 9,22,23 y ocasionalmente puede estar asociada con síndromes polimalformativos [24][25][26] . La existencia de ureterocele o uréter ectópico está bien documentado en la duplicidad ureteral y de igual forma sucede en la triplicidad 9, 17,23,[27][28][29][30] , especialmente aquél último, lo que traduce su frecuente asociación con el reflujo vesicoureteral 11,12,17,23,29,[31][32][33] y la obstrucción 22,33 .…”
Section: Discussionunclassified
“…In the context of complete duplication, the affected kidney is typically divided into two moieties (upper and lower) that are anatomically and functionally grouped to drain into a single collecting system and ureter; each ureter has a separate ureteric insertion (41) (Fig 12). Triplication and even quadruplication of the upper urinary tract can also occur (42).…”
Section: Upper Urinary Tracts (Renal Collecting Systems and Ureters)mentioning
confidence: 97%